Characterization of maize populations in different environmental conditions by means of Three-Mode Principal Components Analysis - Marticorena, Marta; Bramardi, Sergio; Defacio, Raquel Alicia (Facultad de Agronomía e Ingeniería Forestal, Pontificia Universidad Católica de Chile, 2021)
Characterization of 31 native populations of maize conserved at the germplasm bank of the INTA Pergamino Experimental Station, Argentina, was achieved by evaluating 10 quantitative attributes in two different environmental situations. The experimental design generated three-way or three-mode data, repeated observations of a set of attributes for a set of individuals in different conditions. The information was displayed in a three-dimensional array, and the structure of the data was explored using Three-Mode Principal Component Analysis, the Tucker-2 Model. A group of populations was identified that displayed homogeneous behavior in the two environments with respect to the following traits: ear length, prolificacy, grains per meter, yield and 1000 kernel weight. However, another group of populations displayed opposite behavior for the traits of plant height and ear insertion height in the different environment conditions and is indicative of the existence of genotype-environment interaction. In conclusion, Three-Mode Principal Component Analysis is an important tool for characterizing plant genetic resources when their phenotypic values are likely to be affected by environmental conditions.